Investigating Motivational Factors and Strategies for Learning English as a Foreign Language (EFL) among Adult Learners: A Case Study of Indonesian EFL Learners - Rahmayana, Rahmayana; Kharisma, Adib Jasni; Alamsyah, Bambang Nur (Universitas Pahlawan Tuanku Tambusai, 2024)
English is a subject that requires acquisition due to its continued relevance in the contemporary global context. Consequently, this research examines the primary motivational factors driving adult learners to engage in foreign language studies and the strategies they employ to enhance their language proficiency through the use of case studies. Utilizing a mixed-method research design, the investigation incorporated questionnaires and interpreting data with a total of 30 adult EFL learners. The findings derived from the questionnaire revealed statistically significant results. Findings indicate a notable emphasis on motivational factors such as the necessity for global communication and professional growth as the primary motivators, while effective learning tactics encompass the utilization of digital resources, organized speaking exercises, and participation in hands-on activities. This study offers valuable insights on enhancing motivation and efficacy in acquiring English as a Foreign Language for adult learners, particularly within the Indonesian educational context.